Upaya Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Meronce dengan Media Kalender Bekas Anak Kelompok A TK Negeri Gayamsari Kota Semarang Semester II Tahun Ajaran 2022 / 2023 - Surahmi Surahmi (Simpati, 2023)
In early childhood, a child has high energy. This energy is needed to perform various activities to improve physical skills related to fine motor skills, such as shaping or manipulating from clay/wax/dough, drawing, coloring, sticking, cutting, cutting, stringing objects with thread (meronce). These activities serve to train coordination between eyes and hands, which can be developed through play activities (Sumantri, 2005: 145).